Critical Thinking in ELT: Theory and Practice - Irawati, Lulus (English Teaching Journal, 2014)
Critical thinking may be considered as an essential substance contributing to the success of students learning a language, in this English. Some skills in English such as listening, speaking, reading and writing can be successfully achieved whenever students were critical, since critical thinking is also the ability allowing the students to express everything freely. Unfortunately, utilizing critical thinking is not as simple as seen. There should be a regular and consistent process done to encourage the students to be critical. Thus, some approaches, methods, techniques or media need to be applied in order to succeed the achievement of being critical thinkers. Thus, this paper reveals some theories and practices based on reviewing some articles of critical thinking in English Language Teaching (ELT).